(untitled) (Bangladesh Veterinarian, 2025)
This study aimed to evaluate the effects of extenders using skim milk from different species on sperm quality during storage at 5°C over time. Eight ejaculates were preserved in each of five home-made semen extenders: cow skimmed milk (CSM), goat skimmed milk (GSM), sheep skimmed milk (SSM), buffalo skimmed milk (BSM) and commercial dried skim milk (CDSM). Sperm motility, plasma membrane integrity, and normal morphology (%) were assessed at 0, 24, 48, 72, 96, and 120 hours. At 48, 72, 96, and 120 hours, sperm motility in the GSM extender was higher than in the BSM, SSM, and CDSM extenders. Plasma membrane integrity (%) and normal sperm morphology (%) in the GSM and CSM extenders were significantly higher than in the BSM, SSM, and CDSM extenders at 24, 48, 72, 96 and 120 hours. Overall, motility, membrane integrity, and normal morphology were superior in the GSM extender. Further research is needed to validate sperm quality in relation to lambing rates. Bang. vet. 2025. Vol. 42, No. 1 – 2, 11 – 16